ERANCANGAN INTERIOR PERPUSTAKAAN SEKOLAH MENENGAH KEJURUAN NEGERI 4 PADANG DENGAN KONSEP MINIMALIS STYLE - NURHAYATU NUFUT ALIMIN, Ir. Drs. Heldi, M.Si, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2014)
The room in the library of SMKN 4 Padang who is there now have not been able to fulfill the functions, events and activities optimally to the needs of visitors: teachers, staff, and students. The Problem roots is: the convenience factor, the limitations of space, design space less attractiv, completeness part of space, floors, walls flapon and supporting elements such as mobiler space/ furniture, cabinets, tables, chairs, bookshelves, and arrangement of space as well. Urgency of the problem, needs to be consideration for the school and the main attraction in a scientific study namely the final work: "how is the design of the library SMK Padang 4 representative, effective, and efficient".The purpose of this design is to visualize and realize an interior design library space that is representative, effective, and efficient and has the function of educational institutions and are expected to pay attention to interior design services and facilities of a school library for the development of teaching and learning.The concept used in the interior design of the library stakes through minimalist style approach, this concept is used because of its characteristics are simple and elegant, so it is suitable for the arrangement of the library space is limited and does not require excessive space shades .The method used is the analysis of design approaches 5W +1 H The design of the interior of the library was made by the vast size of the room 8:00 and 12:00 x height of the room from the floor 3:00. The chamber was designed to consider a few things such as: setting circulation space, lighting, air temperature, mobiller, selection of materials and colors to suit the needs of the space into a representative, effective, efficient zoom.Interior design of a good school library is prioritizing convenience of users, simple but can attract attention, and not monotonous in order to attract the devotees teachers, employees, students and other school community to come to the library.Kata Kunci: Perancangan, Interior, Minimalis